Cloning, expression and functional characterization of carp, Cyprinus carpio, estrogen receptors and their differential activations by estrogens. Issue 1 (1st July 2011) - Katsu, Yoshinao; Lange, Anke; Miyagawa, Shinichi; Urushitani, Hiroshi; Tatarazako, Norishisa; Kawashima, Yukio; Tyler, Charles R.; Iguchi, Taisen
ABSTRACT Sex‐steroid hormones are essential for normal reproductive activity in both sexes. Estrogens are necessary for ovarian differentiation during a critical developmental stage in vertebrates and promote the growth and differentiation of the female reproductive system. Importantly, environmental estrogens can influence the reproductive system and have been shown to disrupt gametogenesis in males. To understand the molecular mechanisms of estrogen actions and to evaluate estrogen receptor ligand interactions in the carp, Cyprinus carpio, a species used widely for both field‐ and laboratory‐based studies, we cloned all three carp estrogen receptors (ER; ERα, ERβ1 and ERβ2) and applied an estrogen‐responsive (ERE)‐luciferase reporter assay system to characterize the interactions of these receptors with steroidal and synthetic estrogens. DNA fragments encoding all three ERs in carp, ERα, ERβ1 and ERβ2, were obtained from the ovary using degenerate primer sets and PCR techniques, and full‐length carp ER (cER) cDNAs were then obtained using RACE (rapid amplification of the cDNA end) techniques. Amino acid sequences of cERs showed overall homology of 46% (α vs β1), 49% (α vs β2) and 53% (β1 vs β2). In the transient transfection ERE‐luciferase reporter assay system (using mammalian cells) the cER proteins displayed estrogen‐dependent activation of transcription and cERβ2 showed a higher sensitivity to the natural steroid oestrogen, 17β‐estradiol, than cERα. The assay system developed is a powerful assay for toxicology and provides a tool for future studies examining the receptor–environmental chemical interactions and estrogen‐disrupting mechanisms in carp. The data presented also expand our knowledge of estrogen receptor evolution. Copyright © 2011 John Wiley & Sons, Ltd.